Integrative Model of the Implementation of e-WOM, Destination Image and Intention to Behave - FARIDA, Naili (Journal of Environmental Management and Tourism, 2018)
Abstract This study aims to examine: the influence of e-WOM and perceptions of quality on customer satisfaction and the effect of customer satisfaction and the image of the destinations on the intention to behave. The sample was 150 tourists visiting Sidomukti water spring in Bandungan Semarang Central Java Indonesia. Analysis of this study uses Structural Equation Modeling and PLS software to process the data. The results showed that: (1) e-WOM and perceptions of quality have a positive and significant influence on customer satisfaction, (2) Customer satisfaction has a positive and significant impact on the intention to behave, and (3) image of the destination has a positive and significant impact on the intention to behave.